Defence by duplication: The relation between phenotypic glyphosate resistance and EPSPS gene copy number variation in Amaranthus palmeri. Issue 21 (1st November 2021) - Yakimowski, Sarah B.; Teitel, Zachary; Caruso, Christina M.
Abstract: Gene copy number variation (CNV) has been increasingly associated with organismal responses to environmental stress, but we know little about the quantitative relation between CNV and phenotypic variation. In this study we quantify the relation between variation in EPSPS (5‐enolpyruvylshikimate‐3‐phosphate synthase) copy number using digital drop PCR and variation in phenotypic glyphosate resistance in 22 populations of Amaranthus palmeri (Palmer Amaranth), a range‐expanding agricultural weed. Overall, we detected a significant positive relation between population mean copy number and resistance. The majority of populations exhibited high glyphosate resistance yet maintained low‐resistance individuals, resulting in bimodality in many populations. We also investigated threshold models for the relation between copy number and resistance, and found evidence for a threshold of ~15 EPSPS copies: there was a steep increase in resistance below the threshold, followed by a much shallower increase. Across 924 individuals, as copy number increased the range of variation in resistance decreased, yielding an increasing frequency of high phenotypic resistance individuals. Among populations we detected a decline in variation (s.d.) as mean phenotypic resistance increased from moderate to high, consistent with the prediction that as phenotypic resistance increases in populations, stabilizing selection decreases variation in the trait. Our study demonstrates that populations of A . palmeri can harbour wide variation in EPSPS copy number and phenotypic glyphosate resistance, reflecting the history of, and template for future, resistance evolution.